Depiction of Public Interest Theory Based on the Welfare Economic Concept on Indonesia Regulation - Sharon, Grace; Hutama, Bintang Aulia; Hudiyarahma, Aghnia Risqa; Yustitianingtyas, Levina (Yustisia, 2022)
The theory of public interest has become a long debate, and the philosophical meaning is commonly discussed in various research. Generally, it is equated with the needs or interests of the wider community. Public interest has become an interchangeable term in various concepts, from individual needs as intended in natural law to the development of the latest theory of Utilitarianism. The state as the holder of sovereignty and authority has the obligation to carry out the public interest. However, the meaning of this concept is limited in Indonesia, as stated in several laws, one example is the public interest that is always associated with land regulation. It is undeniable through a conventional concept that the subject of land is understood as an asset that has economic value. However, with the development of the economic concept of existing assets, it is found that the concept of public interest is lagging. Therefore, this research has two main objectives: (1) to provide an overview for the elaboration of the concept of interests that are limited by existing laws and regulations in Indonesia, and (2) to take the essence of the economy for the benefit of the public.